The Representation of Roots in the Spelling of Children With Specific Language Impairment. (January 2014) - Deacon, S. Hélène; Cleave, Patricia L.; Baylis, Julia; Fraser, Jillian; Ingram, Elizabeth; Perlmutter, Signy
Children with Specific Language Impairment (SLI) have demonstrated general spelling and writing difficulties. We investigated the sensitivity of children with SLI to the consistent spelling of root morphemes, a feature to which young typically developing children demonstrate sensitivity. We asked children with SLI and two groups of typically developing children ( n = 17 in each group) to spell the same letter-sound sequence (e.g., win ) as a root, and as a component of inflected, derived, and control words (e.g., win, wins, winner, wink ). Children with SLI and spelling-age-matched children (mean age of 9 and 7 years, respectively) were more accurate and more consistent in spelling the initial sections of the inflected and derived words than of the control words, a pattern that suggests sensitivity to the representation of roots in spelling. The absence of a group-level interaction suggests comparable sensitivity in the two groups. Our results suggest that elementary-school-aged children with SLI are sensitive to the consistent spelling of roots, at least to the extent predicted by their general spelling abilities.